1995
DOI: 10.1029/95wr01139
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Early‐Time and Steady State Single‐Ring Infiltration Under Falling Head Conditions

Abstract: The prediction of infiltration of water into field soils requires measurements of the field-saturated hydraulic conductivity (Kfs) and the matric flux potential corresponding to field saturation (qbm). We develop analytical solutions for (1) early-time, onedimensional infiltration into slowly permeable soils such as clay liners under the conditions of an initial constant head followed by a falling head phase and (2) steady state, threedimensional infiltration into permeable soils under the condition of steady … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 17 publications
0
27
0
1
Order By: Relevance
“…The iterative fitting procedure requires an initial guess value for each parameter, and measurement errors coupled with bad first guesses can give incorrect best fit values. Elrick et al (1995) suggested that the slope, m, of the early data of ln[H(t)] versus t gives a guess value of K fs : K fs ¼ mXG r ð2:104Þ Equation (2.104) was derived from the pressure head component of falling-head infiltration and it is expected to provide a sufficiently accurate initial guess of K fs , provided that m is obtained when the perturbing effects of soil capillarity and gravity, i.e. the second and third term, respectively, on the right hand side of Eq.…”
Section: Steady-state Falling-head Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…The iterative fitting procedure requires an initial guess value for each parameter, and measurement errors coupled with bad first guesses can give incorrect best fit values. Elrick et al (1995) suggested that the slope, m, of the early data of ln[H(t)] versus t gives a guess value of K fs : K fs ¼ mXG r ð2:104Þ Equation (2.104) was derived from the pressure head component of falling-head infiltration and it is expected to provide a sufficiently accurate initial guess of K fs , provided that m is obtained when the perturbing effects of soil capillarity and gravity, i.e. the second and third term, respectively, on the right hand side of Eq.…”
Section: Steady-state Falling-head Methodsmentioning
confidence: 97%
“…(2.105) can be obtained from Eq. (2.103), developed by Elrick et al (1995) for a steady-state falling-head process, under the assumptions that the cross-sectional area of the infiltrometer's cylindrical water reservoir coincides with the infiltration surface and the dimensionless shape factor can be estimated with the approximate relationship of Reynolds and Elrick (1990), i.e. G % G e ¼ 0.316(d/r) + 0.184.…”
Section: Bottomless Bucket Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For constant head procedures see Elrick and Reynolds (1992) and Vauclin et al (1994). For falling head procedures see Elrick et al (1995Elrick et al ( , 2002. APPLIED ENGINEERING INVESTIGATIONS: Applied engineering investigations often require only "ball park" estimates of K fs .…”
Section: Detailed Research Investigationsmentioning
confidence: 99%